CoAl LDH@Ni-MOF-74 S-Scheme Heterojunction for Efficient Hydrogen Evolution - Jin, Zhiliang; Li, Yanbing; Ma, Qingxiang (Transactions of Tianjin University, 2021)
Metal–organic frameworks (MOFs) and layered double hydroxides (LDHs) have been considered to be one of the most promising and worthy hot spot materials to develop advanced catalysts for efficient hydrogen evolution due to their prominent characteristics, including unique structures, environmentally friendly nature, high redox activities, and homogeneously effective utilization of transition metal atoms. In this work, the delicate S-scheme heterojunction photocatalyst, CoAl LDH@Ni-MOF-74, was rationally designed and successfully constructed by coupling Ni-MOF-74 with CoAl LDH based on their peculiar structure, excellent electronic properties, and opposite surface potential for enhancing hydrogen generation activity under visible light irradiation. The CoAl LDH nanolayers evenly and dispersedly load on the surface of Ni-MOF-74. The CoAl LDH@Ni-MOF-74 exhibited higher photocatalytic hydrogen evolution activity compared with Ni-MOF-74 and CoAl LDH alone, mainly because the formation of the CoAl LDH@Ni-MOF-74 S-scheme heterojunction accelerated the recombination of several electrons (from conduction band (CB) of Ni-MOF-74) and holes (from valence band (VB) of CoAl LDH) and prevented the recombination of other electrons (from CB of CoAl LDH) and holes (from VB of Ni-MOF-74).